The Role Of Ultrasound In Diagnosing Uterine Scar Failure In Pregnant Women After Cesarean Section - An Andrey Vladimirovich; Olimjonova Saodatkhon Mahammadjon kizi (Zien Journals, 2023)
The significant frequency of caesarean sections, which in recent years has amounted to 15- 30% or more, leads to an urgent problem - an increase in the number of women of reproductive age who have a scar on the uterus. The postulate "once a caesarean section is always a caesarean section", which is dominant in the management of this contingent of women, should become a thing of the past. According to the authors, the incidence of conservative delivery of women with a scar on the uterus after cesarean section ranges from 30 to 70%. Choice of management tactics Childbirth in such women mainly depends on the condition of the scar on the uterus. Difficulties in assessing the condition of the uterine scar during pregnancy are due to the lack of clinical symptoms and restrictions on the use of objective research methods. According to the authors, such a clinically significant symptom as local tenderness on palpation in the lower abdomen is detected only in 18.3% of cases with scar failure. Methods for examining the condition of the scar on the uterus during pregnancy are very limited, and ultrasound scanning (ultrasound) is practically the only one.
Keywords: uterine scar; niche; istmocele